2022
DOI: 10.7554/elife.73539
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor 1-mediated iron uptake regulates bone mass in mice via osteoclast mitochondria and cytoskeleton

Abstract: Increased intracellular iron spurs mitochondrial biogenesis and respiration to satisfy high-energy demand during osteoclast differentiation and bone-resorbing activities. Transferrin receptor 1 (Tfr1) mediates cellular iron uptake through endocytosis of iron-loaded transferrin and its expression increases during osteoclast differentiation. Nonetheless, the precise functions of Tfr1 and Tfr1-mediated iron uptake in osteoclast biology and skeletal homeostasis remain incompletely understood. To investigate the ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…MGCs have been described having increased numbers of lysosomes decades ago (Sutton & Weiss, 1966 ) and several lines of evidence link v‐ATPase‐dependent lysosomal function to osteoclast multinucleation and function (Lee et al , 2006 ; Duan et al , 2016 ). Similarly, TFRC‐mediated iron uptake induces mitochondrial respiration regulating osteoclast differentiation, mature osteoclast function and bone mass (Ishii et al , 2009 ; Das et al , 2022 ). Hence, lysosomal biogenesis coupled with iron homeostasis is likely to be a ‘metabolic booster’ for specialized functions in multinucleated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…MGCs have been described having increased numbers of lysosomes decades ago (Sutton & Weiss, 1966 ) and several lines of evidence link v‐ATPase‐dependent lysosomal function to osteoclast multinucleation and function (Lee et al , 2006 ; Duan et al , 2016 ). Similarly, TFRC‐mediated iron uptake induces mitochondrial respiration regulating osteoclast differentiation, mature osteoclast function and bone mass (Ishii et al , 2009 ; Das et al , 2022 ). Hence, lysosomal biogenesis coupled with iron homeostasis is likely to be a ‘metabolic booster’ for specialized functions in multinucleated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…MGCs have been described having increased numbers of lysosomes decades ago [75] and several lines of evidence link v-ATPase-dependent lysosomal function to osteoclast multinucleation and function [76, 77]. Similarly, TFRC-mediated iron uptake induces mitochondrial respiration regulating osteoclast differentiation, mature osteoclast function and bone mass [78, 79]. Hence lysosomal biogenesis coupled with iron homeostasis is likely to be a ‘metabolic booster’ for specialized functions in multinucleated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…During osteoclast differentiation, key genes in heme-dependent and TF-dependent iron intake pathways are highly upregulated, and the expression of SLC39A14 (an NTBI iron transporter) and Scara-5 and Tim-2 (ferritin transporters) are either downregulated or undetectable in osteoclast lineage cells. 80 Therefore, osteoclasts primarily obtain iron via TFR1-mediated iron uptake; furthermore, osteoclast differentiation has been demonstrated to be tightly linked to TFR1 activation and enhanced iron uptake. 61 , 62 The RANKL/OPG ratio increases when iron levels are excessive, and osteoclast differentiation and bone resorption are promoted by TFR1-mediated iron absorption.…”
Section: Iron Metabolism In Bone and Cartilagementioning
confidence: 99%
“… 81 , 82 Loss of TFR1 in mature osteoclasts results in a significant reduction in total intracellular iron content (approximately 50%), whereas iron levels in monocytes and osteoclast precursor cells are affected to a lesser degree by TFR1 deficiency. 80 Mechanistically, by activating the Src-Rac1-WAVE regulatory complex axis and inhibiting mitochondrial respiration, TFR1 depletion attenuates the cytoskeletal organization and mitochondrial metabolism of mature osteoclasts in vitro and reduced bone resorption. 80 Several studies have shown that excessive iron-induced bone loss is due to an increased number and heightened activity of mature osteoclasts 83 , 84 Together, these findings suggest that excessive iron might promote osteoclast development and activity, and both can contribute to bone resorption.…”
Section: Iron Metabolism In Bone and Cartilagementioning
confidence: 99%
See 1 more Smart Citation